Gas phase silanization for silicon nanowire sensors and other lab‐on‐a‐chip systems. Issue 4 (19th November 2015) - Steinbach, Annina M.; Sandner, Tanja; Mizaikoff, Boris; Strehle, Steffen
Abstract: Designing a microfabrication process for lab‐on‐a‐chip systems can at times be challenging, and the need to integrate a chemical surface modification reaction into this process can limit the options. Therefore, a robust set‐up and protocol for the gas phase modification has been developed that can be variably integrated into microfabrication processes. The main improvement compared to similar methods is, besides easy and versatile sample handling, the integration of a continuous argon flow percolating through the liquid organosilane, and impinging directly the surface tobe modified. This measure reduces the argon consumption drastically compared to current reaction schemes, while keeping short reaction periods. Silicon substrates were modified using 3‐mercaptopropyltrimethoxysilane (MPTMS) and 3‐aminopropyltrimethoxysilane (APTMS), thoroughly studied for different reaction stages, and compared to surfaces modified via a common solvent‐based procedure from isopropanolic solution. Water contact angle measurements, infrared spectroscopy, X‐ray photoelectron spectroscopy, and atomic force microscopy verified the successful deposition of the alkylsilane. Additionally, silicon nanowires were assembled, exemplary for a lab‐on‐a‐chip system, in a liquid gate field‐effect‐transistor configuration, and electrically characterized. The devices showed the expected response to applied liquid gate potentials before and after the modification and exhibited characteristic changes in the transconductance curve. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)